Does the Form Serve Surviving? The Experience of Inheriting the Memory of the Holocaust and Psychological Functions of It’s Narrativization in Prose of Magdalena Tulli - Адельгейм, Ирина (Poznańskie Studia Slawistyczne, 2019)
The article considers the experience of inheriting the traumatic memory in prose of Magdalena Tulli and autopsychotherapeutic functions of it’s narrativization with the help of elements of psychotherapeutic methods (family constellations, a dialogue with a child in yourself, deconstruction and reconstruction of the life narratives, re-membering, therapeutic metaphor, focusing). The narrativization of the trauma in the process of artistic narration contributes processing traumatic experience, is an important element of constructing of autobiography, gives a chance to retrieve own history, which is not overshadowed with tragic parental discourse, helps to achieve balance between traumatic and positive contents of autobiographical memory, fulfills interpsychological functions.